MAQASHID SYARI’AH DALAM TRADISI SAPRAHAN PADA WALIMATUL URSY DI DESA PURINGAN KECAMATAN TELUK KERAMAT KABUPATEN SAMBAS - Jariah, Ainun; Achmad, Firdaus; Ulya, Nanda Himmatul (Al-Usroh, 2024)
The saprahan tradition is an often held at some events, in the reality of execution it requires a review of Islamic law like maqashid shari'ah because there are no definite dalil in the qur'an and the hadith that directly describes the saprahan tradition. The purpose of this study is: 1) to know the practice of the saprahan tradition of walimatul ursy in the purgatory bay district of sambass.2) to know the aspect of maqashid Shari 'ah in the saprahan tradition of walimatul ursy in the purgatory bay district of sambas. The study is field research by using descriptive methods that approach through a qualitative approach. The data sources used in the study used the primary data of interviews with puringan village people. Then for the secondary data used were books, journals, qur'an, the hadith. As for the data analysis techniques used through the 3 stages are data reduction, data discipline, and deduction and deduction. The results in the study were: 1) during preparation until the implementation of the saprahan tradition was always accompanied by good habits consistent with Islamic rules. The tradition of saprahan at regular weddings is always carried out in a long tent called taruf. 2) the maqashid Shari 'ah aspect of the wearisome tradition of walimatul ursy in the old bay district district isa hajiyat state, as is the custom of saprahan supporting the implementation of marriage in the purpur village, where marriage forms a means of maintaining nasab that is a need for dharuriyat while the sitting and eating of saprahan become a tahcinate need to complete the alignment of the saprahan implementation. Furthermore another aspect of maqashid Shari 'ah on the tradition of saprahan is the maintaining of possessions.